2007
DOI: 10.1016/j.ejcts.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of randomized control trials comparing minimally invasive direct coronary bypass grafting versus percutaneous coronary intervention for stenosis of the proximal left anterior descending artery

Abstract: Percutaneous intervention (PCI) and minimally invasive direct coronary bypass grafting (MIDCAB) are both well-accepted treatment options for isolated high-grade stenosis of proximal left anterior descending coronary artery. Small studies comparing the two modalities have yielded conflicting results. We performed a meta-analysis of randomized control trials to compare percutaneous intervention with minimally invasive coronary bypass grafting for isolated proximal left anterior descending artery stenosis. Five r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 32 publications
1
36
0
6
Order By: Relevance
“…In the 1970s and 1980s, 3 RCTs established the survival benefit of CABG compared with contemporaneous (although minimal by current standards) medical therapy without revascularization in certain subjects with stable angina: the Veter-ans Affairs Cooperative Study, 114 European Coronary Surgery Study, 55 and CASS (Coronary Artery Surgery Study). 115 Subsequently, a 1994 meta-analysis of 7 studies that randomized a total of 2649 patients to medical therapy or CABG 30 showed that CABG offered a survival advantage over medical therapy for patients with left main or 3-vessel CAD.…”
Section: Cabg Versus Contemporaneous Medical Therapymentioning
confidence: 99%
“…In the 1970s and 1980s, 3 RCTs established the survival benefit of CABG compared with contemporaneous (although minimal by current standards) medical therapy without revascularization in certain subjects with stable angina: the Veter-ans Affairs Cooperative Study, 114 European Coronary Surgery Study, 55 and CASS (Coronary Artery Surgery Study). 115 Subsequently, a 1994 meta-analysis of 7 studies that randomized a total of 2649 patients to medical therapy or CABG 30 showed that CABG offered a survival advantage over medical therapy for patients with left main or 3-vessel CAD.…”
Section: Cabg Versus Contemporaneous Medical Therapymentioning
confidence: 99%
“…69,[72][73][74][75][76][77][78][79][80][81][82][83] A retrospective cohort study of 14 766 consecutive patients undergoing isolated CABG identified a mortality benefit (OR: 0.45) for off-pump CABG in patients with a predicted risk of mortality Ͼ2.5%, 82 but a subsequent randomized comparison of off-pump CABG to traditional on-pump CABG in 341 high-risk patients (a Euroscore Ͼ5) showed no difference in the composite endpoint of all-cause death, acute MI, stroke, or a required reintervention procedure. 78 An analysis of data from the New York State Cardiac Surgery Reporting system did not demonstrate a reduction in mortality rate with off-pump CABG in any patient subgroup, including the elderly (age Ͼ80 years) or those with cerebrovascular disease, azotemia, or an extensively calcified ascending aorta.…”
Section: Off-pump Cabg Versus Traditional On-pump Cabgmentioning
confidence: 99%
“…Established treatment options for isolated proximal LAD lesions are minimally invasive direct coronary artery bypass (MIDCAB) surgery with the left internal mammary artery (LIMA) as bypass graft and percutaneous coronary intervention (PCI) with bare-metal stents (3,4). Both treatment strategies effectively reduce symptoms (3).…”
Section: Discussionmentioning
confidence: 99%